Pyroprocessing 공정에 사용되는 전해반응장치의 규모 확대 - 유재형; 김정국; 이한수 (Journal of nuclear fuel cycle and waste technology (Online), 2009)
Pyroprocessing에 의한 사용후핵연료 처리 과정에서 핵연료 물질은 전해정련장치, 전해환원장치, 전해제 련장치의 전해조에서 전극 표면에서의 전기화학반응과 전해질의 교반을 통해서 회수된다. 따라서 이 장치들 은 장차 pyroprocessing의 실용화를 위하여 규모 확대가 필요하다. 본 연구에서는 교반을 수반하는 전해반응 장치를 대규모 장치로 확대코자 할 때 합리적으로 적용할 수 있는 장치규모 확대 기법을 고찰해 보았다. 장치 규모 확대에 있어 장치크기와 전극 표면적의 크기는 기하학적 유사성이 기본적으로 적용되어야 한다. 그밖에 전해질의 유동특성을 좌우하는 기준 가운데 전해질의 단위체적당 에너지 투입량이 동일하다는 기준을 채택 할 경우 시행착오법에 의한 계산절차를 도출해내었으며, 이 계산법은 전해조에서의 적절한 교반속도를 구할수 있게 해 준다. 또 임의의 소규모 전해반응 시스템에 대하여 단위체적당 에너지 투입량이 동일하다는 기준 과 교반기 날개끝 속도가 동일하다는 기준을 적용할 경우 전해조의 규모 확대에 관한 일례를 제시하였다. In the pyroprocessing of spent nuclear fuels, fuel materials are recovered by electrochemical reactions on the surface of electrodes as well as stirring the electrolyte in electrolytic cells such as electrorefiner, electroreducer and electrowinner. The system with this equipment should first be scaled-up in order to commercialize the pyroprocessing. So in this study, the scale-up for those electrolytic cells was studied to design a large-scale system which can be employed in a commercial process in the future. Basically the dimensions of both electrolytic cells and electrodes should be enlarged on the basis of the geometrical similarity. Then the criterion of constant power input per unit volume, characterizing the fluid behavior in the cells, was introduced in this study and a calculation process based on trial-and-error methode was derived, which makes it possible to seek a proper speed of agitation in the electrolytic cells. Consequently examples of scale-up for an arbitrary small scale system were shown when the criterion of constant power input per unit volume and another criterion of constant impeller tip speed were respectively applied. KCI Citation Count: 0